THE INFLUENCE OF SOCIAL, LIFESTYLE, DIGITAL FINANCIAL LITERACY, AND EASE OF USE ON DIGITAL PAYMENT USE AMONG GEN Z - Irabi’ah Al Adawiyah; Anna Widiastuti (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the effects of social influence, lifestyle, digital financial literacy, and perceived ease of use on the adoption of digital payment methods among Generation Z in Jepara Regency. As a cohort widely recognized for its technological proficiency, Generation Z represents the primary user base of digital financial services. Employing a quantitative research design, data were collected through questionnaires distributed to 128 income-earning Gen Z respondents. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that lifestyle and perceived ease of use have a positive and significant effect on digital payment adoption. Conversely, social influence and digital financial literacy do not show a significant impact. These findings suggest that Generation Z’s adoption of digital payment systems is driven mainly by practical considerations and digitally oriented lifestyles rather than social pressure or financial knowledge. This study contributes to the understanding of young generations’ financial behavior in the digital era and offers insights for the development of more user-oriented digital financial services, as well as directions for future research. Keywords: Digital payment; Generation Z; Lifestyle; Digital financial literacy; Ease of Use